PENGINTEGRASIAN AJARAN TRI NGA MELALUI PEMBELAJARAN SBDP SUB SENI MUSIK SEBAGAI PENANAMAN KARAKTER BUDAYA BAIK DI SDN 2 WALUYO - Ulfa Diana, Anissa; Susanto, Rusnoto; Wahyu Astuti, Avinda; Septiyani, Lina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Ki Hadjar Dewantara's thoughts on education have become a distinctive image for the history of education in Indonesia. Ki Hadjar Dewantara's educational concept displays the uniqueness of Indonesian culture. One of Ki Hadjar's teaching methods is Tri Nga (understand, feel and act). Furthermore, Ki Hadjar Dewantara said, what is called